KEANEKARAGAMAN JENIS AVIFAUNA DIURNAL PADA LAHAN BEKAS KEBAKARAN DI DESA RASAU JAYA UMUM KABUPATEN KUBU RAYA - Mukhtamar, Ahmad; Prayogo, Hari; Anwari, M Sofwan (Universitas Tanjungpura, 2019)
Avifauna in its habitat decereasing by many factor such as land clearing which cause avifauna becomes endangered,moreover illegal hunting dangering population of avifauna in its own habitat,and furthermore factors which may cause deleterious of nature. The aims of this research is to collect the data of diurnal avifauna diversity in the ex-fire areas in Rasau Jaya Umum village Kubu Raya regency. This research is use point count methode that used ex-fire areas and un-fire areas, in the morning, noon and afternoon with 3 times repeatly of each location. The results showed that observation of avifauna ex-fire areas in 2014, 2016, 2017, 2018 and un-fire areas found 20 species from 16 families with a total of 160 individuals. Dominance value of five location possess average value of C close 0, so that indicates there is no species dominates another species,which mean function of avifauna species which had discovered in that location is even and stable. Diversity index avifauna species which discoverd from five location has shown average criteria avifauna species differ from each location depends on environtment condition.eveness index of ex burnt land from 2014, 2016 and 2017 consist eveness value and its abundance had categorized by unstable community or not even. Encounter degree of avifauna which categorized of five location, had shown avifauna from Hirundo rustica, Lonchura malacca and Collocalia esculenta high rate of encounter degree its species because enviromental condition which helps avifauna for its reproduction, feeding ground and nesting, avifauna eveness index found un-fire (TT) and ex-fire areas in 2014, 2016, 2017, 2018, have 3 criteria,which is low (TT-2017 and TT-2018)Â average TT-2014, TT-2016, 2014-2018 and 2016-2018) and high (2014-2016, 2014-2017, 2016-2017 and 2017-2018).Keywords : Avifauna, Species diversity, Ex- burn forest.